Identifying Racial Differences in Vocational Rehabilitation Services. (October 2022) - Yin, Michelle; Pathak, Aditi; Lin, Dajun; Dizdari, Nevin
The literature on racial differences in vocational rehabilitation (VR) services has not been updated for over a decade. Using the 2017 individual-level U.S. national RSA-911 data, supplemented with the 2017 American Community Survey and publicly available information from the Kaiser Family Foundation, we investigated racial differences at each step of the VR process—application, eligibility, service provision, and employment outcomes at closure. At the first step, application, White individuals with disabilities were less likely to apply than their African American, American Indian/Alaska Native, and Hispanic counterparts, and more likely to apply than their Asian counterparts. For the remaining three steps, the results were inverted: the White subgroup had higher eligibility rates, service rates, and employment rates than the African American, American Indian/Alaska Native, and Hispanic subgroups, and lower rates than the Asian subgroup. These findings suggest that racial and ethnic differences continue to exist in the VR process despite several legislative acts and policy efforts. Within each racial and ethnic minority group, we also found large variation in application rates and employment rates across states, which indicates a need for developing performance measures and standardized guidelines for state VR agencies to better serve individuals with disabilities from racial and ethnic minorities.